Dramatic response to brentuximab vedotin in refractory nontransformed CD30– mycosis fungoides allowing allogeneic stem cell transplant and long‐term complete remission. (1st January 2019) - Mahévas, T.; Ram‐Wolff, C.; Battistella, M.; Pennamen, M.D.V.; Rivet, J.; Brice, P.; Bagot, M.
Summary: The erythrodermic ulcerated form of mycosis fungoides (MF) is exceptional, and treatment of refractory cases is challenging. Brentuximab vedotin (BV) is a monoclonal antibody combined with monomethyl auristatin E, recently approved for the treatment of refractory CD30 + cutaneous T‐cell lymphoma. We report a case of refractory MF in a 56‐year‐old man with a long history of large‐plaque parapsoriasis, as revealed by psoriasiform erythroderma, treated initially with cyclophosphamide, doxorubicin, vincristine and prednisone (CHOP) polychemotherapy, inducing a 2‐year complete response. After relapse, interferon and gemcitabine were unsuccessful. Finally, treatment with BV was decided upon, despite the absence of CD30 expression. After three infusions of BV 1·8 mg kg −1, we achieved a complete and stable response, allowing an allogeneic stem cell transplant. The patient is still in complete remission, 19 months after the graft. This case illustrates the possibility of using BV in refractory CD30 – MF as a salvage therapy. Abstract : What's already known about this topic? The efficiency of brentuximab vedotin in refractory CD30 + cutaneous T‐cell lymphoma is well established. Erythrodermic forms of MF are challenging to treat, and allogeneic stem cell transplant is sometimes required. What does this study add? This psoriasiform, ulcerated and erythrodermic clinical presentation of MF is exceptional, and the response to brentuximab vedotin, despite the absence of CD30 expression on skin biopsy, allowed us to perform an allogeneic stem cell transplant, inducing long‐term complete remission. Linked Comment:  Sun and Wang. Br J Dermatol 2019; 180 :1300–1301 .